O uso de medicamentos e de outros remédios por graduandos de enfermagem - Lima, Carlos Túlio Alencar (Universidade Federal do Tocantins, 2021)
INTRODUCTION: Different kinds of medicines, can be used to heal diseases or relieve symptons. The medicine use must be rational because adverse reactions are inherent in its use. Besides, teas or medicinal plants may interact with medicines consumed, which risks can be aggravated by the self medication. OBJECTIVE: To investigate the use of medicines and other remedies by nursing senior students. METHODS: Cross-sectional study, on which its participants were nursing students from the Universidade Federal do Tocantins (Tocantins Federal University). The data were collected through a questionnaire (2° semester/2018), organized in Excel® spreadsheets and analyzed through descriptive statistic. The project was approved by the Comitê de Ética em Pesquisa (CAAE 90998318.0.0000.5519), the Research Ethics Committee. RESULTS: Participated 76 academics with an average age of 22,28 years old (standard deviation: 3,43) that in the majority were black and brown (61,83%) and womankind (84%). Between the participants 32,89% had claimed health problems, 38,15% the daily use of medicines and, approximately, 90% reported self medication (34,20% were weekly or monthly self medication) and 48,66% didn’t know the totality of medicines they claimed to consume. The oral contraceptive pill was the most daily used medicine (44,82%), followed by isotretinoin (10,34%) and Metamizole (10,34%). About the consumption of other remedies is possible to observe the predominance of teas (35,52%), followed by plants (5,2%), honey and garrafadas, a sort of bottled homemade medicine, (3,94%). CONCLUSION: About 38% of academics consume medicines daily, 35% use teas and 90% self medication. These practices can threaten the health of those academics of nursing. In addition, at the end of the curse, they will be part of the health team and they personal practices can apply they professional practice.